Al Jinās Dan Al Saja’ Fii Kitāb Washāya Al Abā Li Al Abnā - Silmy, Ahmad Nahidl; Awaliyah, Nurul Aida; Setiyadi, Alif Cahya; Isnainurrohman, Abdillah (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
The study of rhetoric is one of the sciences that studies how to process words or sentences in the Arabic language that are beautiful because they have clear meanings, and the style of the language used must be in accordance with the situation and conditions. There are three divisions in rhetoric: the science of meanings, the science of eloquence, and the science of ingenuity. In the science of ingenuity, the researcher chose alliteration and assonance. The aims of this study are: 1.Definition How many Jinas and Sajak in the book of commandments of fathers to children. 2.Definition of the types of  Jinas and Sajak in the book Fathers' Commandments to Sons. The library study is based on reading books, magazines, or other research sources to collect data, and the researcher needs deep thinking to get a good research result, then she reads the books and continues to analyze the books in terms of rhetoric.